Strategies to Mitigate Mental Health Problems in Adolescents through Self-Care Gamification Platform - Xavier Kharis; J. Johny Natu Prihanto; Amanda Setiorini (Studi Ilmu Manajemen dan Organisasi, 2025)
Purpose: This study aims to explore how technology can help address mental health challenges faced by adolescents in educational environments. It focuses on how digital tools assist educators in identifying, managing, and supporting students’ mental well-being. Methodology: A qualitative research design was employed using purposive sampling to select participants. Data were collected through semi-structured interviews and analyzed using an interpretative approach to understand participants’ perceptions and experiences related to the use of technology in supporting mental health. Results: The findings show that technology aids educators in recognizing and responding to students’ mental health concerns, enhances awareness, and increases engagement in mental health initiatives. Digital platforms, such as online counseling, mental health applications, and virtual discussion spaces, help reduce stigma and promote open communication among students. Conclusions: Technology has significant potential to support mental health efforts in schools by empowering educators and fostering active student participation in mental health programs. It serves as an effective medium for early detection, awareness building, and emotional support. Limitations: The study’s limitations include a small number of participants and a focus on a single educational setting, which may limit the generalizability of the findings. Contribution: This research provides practical insights for educators, policymakers, and mental health professionals on how to integrate technology-based approaches into school mental health strategies to create supportive and inclusive learning environments.